Analysis of prediction and early warning indexes of patients with COVID-19. (1st December 2020) - Song, Lu; Dong, Yongkang; Xu, Ming; Shi, Dongwu; Guo, Wei; Li, Yaojun; Zhang, Xinri; Ma, Xia
ABSTRACT: Background: The aim was to compare the laboratory data of patients with suspected and confirmed new coronavirus pneumonia (COVID-19) and look for diagnostic predictive and early warning indicators, which will help to better manage the disease. Methods: A total of 36 confirmed COVID-19 patients were divided into the general (n = 17) and critical group (n = 19). The suspected group enrolled 23 suspected COVID-19 patients with the negative nucleic acid test result. We collected all patients' clinical characteristics and some laboratory indicators at the time of admission and conducted Logistic regression analysis after comparing the differences between groups. Results: There were no significant differences in age, gender, disease duration, fever history, and comorbidities between the suspected and general group (P > 0.05); however, fibrinogen was statistically different (P < 0.05). Compared with the general group, the oxygenation index and lymphocytes were significantly reduced and the Neutrophil-to-lymphocyte Ratio (NLR) and total bilirubin were increased in the critical group (P < 0.05). The fibrinogen OR value was 2.52 (95% CI 1.18–5.36, P = 0.017) and the NLR OR value was 2.91 (95% CI 1.36–6.21, P = 0.006). Conclusions: Fibrinogen is a valuable diagnostic predictor for patients with suspected COVID-19. For confirmed COVID-19 patients, the NLR is a valuable early warning indicator.